A 40-weeks ovarian pregnancy: a case report - Massena, Larry M.; S. Louis, Allrich; Emile, Richcardeau; Millien, Christophe (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian pregnancy is a rare ectopic pregnancy, often misdiagnosed at advanced gestational age. We present a case of a 38-year-old woman at 40 weeks with ovarian pregnancy and fetal death, discovered during laparotomy at Mirebalais Teaching Hospital, Haiti. The patient presented with abdominal pain, light vaginal bleeding, and high blood pressure. Ultrasound suggested intrauterine fetal death and placenta previa, but the laparotomy revealed a non-gravid uterus and a large amniotic sac in the left ovary, suggesting a term ovarian pregnancy. A left adnexectomy was performed, and histopathology confirmed the diagnosis based on the Spiegelberg criteria. Despite complications, the patient had a good outcome. This case emphasizes the diagnostic challenges and the importance of early prenatal care to prevent complications life-threatening associated with advanced ovarian pregnancies.